2022
DOI: 10.1007/s12311-022-01462-9
|View full text |Cite
|
Sign up to set email alerts
|

ClearSpeechTogether: a Rater Blinded, Single, Controlled Feasibility Study of Speech Intervention for People with Progressive Ataxia

Abstract: Background Progressive ataxias frequently lead to speech disorders and consequently impact on communication participation and psychosocial wellbeing. Whilst recent studies demonstrate the potential for improvements in these areas, these treatments generally require intensive input which can reduce acceptability of the approach. A new model of care—ClearSpeechTogether—is proposed which maximises treatment intensity whilst minimising demands on clinician. This study aimed to establish… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 57 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…This is inclusive of pre, post, and follow-up assessments. Arm 1 will involve ClearSpeechTogether, a speech therapy approach originally piloted with speakers with progressive ataxia [13]. ClearSpeechTogether is an interactive, patient centric telehealth model of care that combines individual Speech & Language Therapy (SLT) intervention with peer led group therapy.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inclusive of pre, post, and follow-up assessments. Arm 1 will involve ClearSpeechTogether, a speech therapy approach originally piloted with speakers with progressive ataxia [13]. ClearSpeechTogether is an interactive, patient centric telehealth model of care that combines individual Speech & Language Therapy (SLT) intervention with peer led group therapy.…”
Section: Interventionsmentioning
confidence: 99%
“…Using this as a baseline, it is necessary for the study to be have sufficient power to detect a mean increase in CPIB scores of 3.6-points. The previous ClearSpeechTogether pilot [13] had a sample size of 11, and retention of 9 participants. The mean difference between pre and post-therapy assessments in this study was 6.33 points (SD = 1.25).…”
Section: Sample Sizementioning
confidence: 99%
“…The speech characteristics in ataxic dysarthria differ between patients along the aspects of speech production (articulation, voice, nasal resonance, prosody and breathing). Still, recent studies show that there can be positive effects of speech therapy interventions [3][4][5][6], but more than for any other dysarthria, we may have to apply individually tailored rather than standardized speech interventions for patients with ataxic dysarthria.…”
Section: Limitationsmentioning
confidence: 99%
“…A survey by Ataxia UK revealed that speech problems are one of the most frequent symptoms with a high impact [2]. Four recent studies demonstrated that a relatively short and intensive speech therapy program can accomplish positive changes in speech or psychosocial aspects in patients with degenerative ataxia [3][4][5][6]. However, results were inconsistent and the stability or duration of the reported improvements is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation